Linear bounded potential model for semiconductor band bending. (26th January 2022) - Villavicencio, F; Ferreyra, J M; Bridoux, G; Villafuerte, M
Abstract: We propose a simple but unexplored model for the semiconductor band bending with the aim to obtain a relatively simple expression to calculate the energy spectrum for the confined levels and the analytical expressions for wave-functions. This model consists of a linear potential but it is bounded or trimmed in energy unlike the well known wedge potential (WP) model. We present exact solutions for this potential in the frame of the effective mass approximation and they are valid for electron or hole confinement potential. This model provides a more adequate physical scenario than the WP since it takes into account the charge balance involved in the band bending potential. These results allow to treat confined potential problems as in the case of a two-dimensional electron gas in a simplified way. We discuss the application of this approximation to the recombination time of electrons an holes and for the Franz–Keldysh effect.